IBM PENGEMBANGAN MEDIA PEMBELAJARAN JARAK JAUH BERBASIS KURIKULUM MERDEKA BELAJAR DI SDN 5 KARANGSARI BANYUWANGI - Siska Aprilia Hardiyanti; Aprilia Divi Yustita; Eka Afrida Ermawati (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The outbreak of the Covid-19 pandemic has impacted the public sector with various problems and crises, including the education sector. The government through the Ministry of Education and Culture (Kemendikbud) finally implemented a learning from home (LFH) policy and the implementation of an independent learning curriculum (Kurikulum Merdeka Belajar). The independent learning curriculum was created as an answer to many complaints about Indonesian education system. The independent learning curriculum has a concept in building a national education system and returns to the essence of the law by giving freedom to the academic community starting from teachers as the driving force of national education. The purpose of this service activity is to assist teachers in understanding the nature of Kurikulum Merdeka Belajar and to create learning media that are relevant to the curriculum by maximizing the use of information and communication technology used in everyday life. The method used in this service is the implementation of free learning curriculum workshops and training on the creation of technology-based innovative learning media. As a result of this service, teachers are able to create interesting learning media and then used inteaching and learning process.